2010
DOI: 10.1016/j.trb.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The continuous cross-nested logit model: Formulation and application for departure time choice

Abstract: Discrete choice models, like the multinomial logit (MNL), have long been recognized for their ability to capture a wide array of transport-related choice phenomena. However, a number of choices are continuous response variables (e.g., location choice, departure time choice, activity duration, and vehicle usage). In this paper, the continuous cross-nested logit (CCNL) model is introduced. The CCNL model results from generalizing the discrete cross-nested logit (CNL) model for a continuous response variable, muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 26 publications
0
21
0
2
Order By: Relevance
“…Choices in a continuous setting instead have been often described by models based on hazard functions; but such an approach is criticized because it lacks a proper behavioural support. Recently Lemp et al (2010) suggested a continuous cross-nested logit model, which retains the behavioural justification of the logit models and allows for correlation across alternatives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Choices in a continuous setting instead have been often described by models based on hazard functions; but such an approach is criticized because it lacks a proper behavioural support. Recently Lemp et al (2010) suggested a continuous cross-nested logit model, which retains the behavioural justification of the logit models and allows for correlation across alternatives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of the departure time analysis, there has been extensive research applying the theory of rational behavior, such as the bottleneck model (14) and discrete departure time choice models (25)(26)(27)(28). Under rational behavior theory, travelers have access to information about all feasible alternatives and maximize their utility (29).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These various approaches include the use of discrete (see, e.g. Small 1982) versus continuous time models (Wang 1996, van Vuren et al 1999; model structures ranging from logit to other more general models such as nested logit (Brownstone and Small 1989), ordered generalised extreme value (Small 1987), bivariate and multinomial probit (Liu andMahmassani 1998, Lemp et al 2011), error components logit (Bhat 1998, de Jong et al 2003, RAND Europe 2005, Hess et al 2007, Holyoak 2007, Kristoffersson and Engelson 2008, continuous hazard-based logit (Bhat and Steed 2002), continuous cross-nested logit (Lemp et al 2010), and the presence of schedule delay terms, generally available from stated preferences but not revealed preferences surveys (see, e.g. de Jong et al 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other papers apply only the cyclicality property (see, e.g. Lemp et al 2010). Carrier (2008) models time-of-travel choice for airline travellers by using trigonometric functions to represent time as a continuous variable.…”
Section: Contributions and Organisationmentioning
confidence: 99%